Octomeria lilliputana (Orchidaceae), a new species from Brazilian Atlantic Forest, State of Paraná, Brazil - Forster, Wellington; Souza, Vinicius Castro; de Barros, Fábio (Phytotaxa, 2013)
While conducting a taxonomic revision of Octomeria, a new species from the Atlantic Forest biome, in Paraná State, Brazil was found. The species is here described and illustrated as Octomeria lilliputana. Based on morphological characters, this species belongs to Octomeria section Octomeria subsection Octomeria. The species is provisionally ascribed to the Data Deficient (DD) category of IUCN.